Land of the long white cloud : Maori myths, tales, and legends - Te Kanawa, Kiri (Arcade Pub., 1989)
A collection of nineteen tales from various Maori tribes of New Zealand about the trickster Maui, the Creation, monsters, birds, animals, and special places.